Pelatihan Penulisan Surat Dinas di Kantor Camat Jayaloka Kabupaten Musi Rawas - Sulastri Ningsih; Herma Yunita (Lembaga Pengembangan Kinerja Dosen, 2026)
Office administration plays a crucial role in ensuring effective and efficient government operations and the delivery of quality public services (Muniarty et al., 2022). In Indonesia, the ability to write official correspondence correctly is a fundamental competency for civil servants, particularly those working at the sub-district level, as they serve as the frontline of public administration (Aktifa et al., 2023). Well-written official letters reflect professionalism, support administrative efficiency, and strengthen public trust in government institutions.The Jayaloka Sub-district Office in Musi Rawas Regency is responsible for handling various administrative documents, including certificates, letters of introduction, decrees, and other official correspondence. Preliminary observations revealed that the office processes approximately 50–70 incoming and outgoing letters each week, indicating a high volume of administrative activities that require accurate and systematic correspondence management. Despite its importance, errors in official letter writing remain common in government institutions, including mistakes in formatting, language usage, and document selection (Syuhada et al., 2021). These issues may reduce institutional credibility, create misunderstandings, and even result in legal consequences (Tatema Telaumbanua et al., 2023). Therefore, improving official letter writing skills is essential to support good governance, enhance administrative professionalism, and provide transparent, accountable, and high-quality public services (Herlina, 2022)